962Adolescent Alcohol Use Trajectories: A Prospective Study of Risk Factors and Adulthood AUD Outcomes. (2nd September 2021) - Yuen, Wing See; Chan, Gary; Clare, Philip; Bruno, Raimondo; Boland, Veronica; Aiken, Alexandra; Kypri, Kypros; Horwood, John; McCambridge, Jim; Degenhardt, Louisa; Slade, Tim; Wadolowski, Monika; et al.
Abstract: Background: Adolescents often display heterogenous trajectories of alcohol use. Initiation and escalation of drinking may be an important predictor of later harms. Previous attempts to conceptualise these trajectories lacked adjustment for known confounders of adolescent drinking, which our study has aimed to address by modelling dynamic changes in drinking whilst adjusting for parent, child, and peer factors. Methods: Survey data from a longitudinal cohort of Australian adolescents (n = 1813) were used to model latent class alcohol use trajectories over five annual follow-ups ( M age =13.9 and 17.8 years). Regression models determined whether child, parent, and peer factors at baseline ( M age =12.9 years) predicted trajectory membership and whether trajectories predicted self-reported symptoms of AUD in early adulthood ( M age =18.8 years). Results: We identified a four‐class solution: abstaining (n = 352); late-onset moderate drinking (n = 503); early-onset moderate drinking (n = 663); and early-onset heavy drinking (n = 295). Alcohol-specific household rules reduced risk of early-onset heavy drinking compared to late-onset moderate drinking (RRR: 0.31; 99.5% CI: 0.11, 0.83), whereas substance-using peers increased this risk (RRR: 3.43; 99.5% CI: 2.10, 5.62). Early-onset heavy drinking increased odds of meeting criteria for AUD in early adulthood (OR: 7.68; 99.5% CI: 2.41, 24.47). Conclusions: Our study provides evidence that early initiation and heavy alcohol use throughout adolescence is associated with increased risk of alcohol-related harm compared to recommended maximum levels of consumption (late-onset, moderate drinking). Key messages: Parenting factors and peer influences in early adolescence should be considered to reduce risk of early initiation and heavy drinking, which in turn reduces risk of later harm.